Preizkus seznama izbranih kategorij MKF v ambulanti za protetiko in ortotiko - Kavčič, Barbara (Rehabilitacija (Ljubljana), 2010)
Method: We examined the medical documentation of 35 patients from the outpatient service for prosthetics and orthotics who had different medical conditions, and chose the suitable ICF categories from all four chapters of the ICF at the second level. Results: We observed the categories from all sections of the ICF in all the chosen patients, from 8 to 20 categories per patient, 15 on average. The largest number of categories was opened in the Body Functions section (from 2 to 10 per patient) and in the Activities and Participation section (from 1 to 9 per patient). Among Environmental Factors, 1 to 5 categories were opened per patient. The majority of patients had a facilitator as an Environmental Factor. Conclusions: Even though patients at the outpatient service for prosthetics and orthotics have various medical and posttraumatic conditions, the list of categories of the ICF based on the suggestions of an ideal and minimal set of the ICF data (Appendix 9 ICF) can cover the majority of the problems that patients at such outpatient service are faced with.
Keywords: amputacija; diagnostika; invalidi; ocenjevanje; protetika; rehabilitacija; vocational rehabilitation; zdravje; zmožnosti